2017
DOI: 10.1186/s13173-017-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Overview and open issues on penetration test

Abstract: Several studies regarding security testing for corporate environments, networks, and systems were developed in the past years. Therefore, to understand how methodologies and tools for security testing have evolved is an important task. One of the reasons for this evolution is due to penetration test, also known as Pentest. The main objective of this work is to provide an overview on Pentest, showing its application scenarios, models, methodologies, and tools from published papers. Thereby, this work may help r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The content of this section revolves around examining and discussing the results of the preceding section. Based on the results derived from this research, it was found that only a very small number of surveys and overviews have been conducted on Black-box web vulnerability scanners; a majority of them revolve around merely summarizing the concepts of the approaches without targeting their characteristics and effectiveness [18], [55], [65], [78]. However, the present study contains a systematic literature review on the most cited web vulnerability scanners, summarizing their characteristics and discussing the results of different evaluation studies conducted to compare their effectiveness in detecting the common web applications vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of this section revolves around examining and discussing the results of the preceding section. Based on the results derived from this research, it was found that only a very small number of surveys and overviews have been conducted on Black-box web vulnerability scanners; a majority of them revolve around merely summarizing the concepts of the approaches without targeting their characteristics and effectiveness [18], [55], [65], [78]. However, the present study contains a systematic literature review on the most cited web vulnerability scanners, summarizing their characteristics and discussing the results of different evaluation studies conducted to compare their effectiveness in detecting the common web applications vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few surveys and overviews on Black-box web vulnerability scanners were returned by this research. Bertoglio and Zorzo [18] systemically reviewed 54 primary studies using quality criteria to selected papers to determine reliability and credibility. The criteria grouped papers as 'Good', ' Very good ', and 'Excellent'.…”
Section: Related Workmentioning
confidence: 99%
“…Work [5] proposes a generalized model of security testing in the form of a systematic process map. The possibilities to categorize software safety risks have been described, as well as building the tables to prioritize the tasks on minimizing these risks.…”
Section: The Aim and Objectives Of The Studymentioning
confidence: 99%
“…to execute the testing preparation processThe polynomial rz 6 -yz5 -dz4 -hz 3 -xz 2 +cz+b generates seven poles. The solution to the following equation…”
mentioning
confidence: 99%
“…It is important to remember that "assessing the security state is a continuous and necessary task to understand the risks there exist. This assessment is usually performed through security tests" [57]. It always comes to a simple rule: the chain is as strong as its weakest link [58].…”
Section: Legality and Ethics Of Conducted Researchmentioning
confidence: 99%